2022
DOI: 10.1590/0102-311xpt192321
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças no padrão de internações e óbitos por COVID-19 após substancial vacinação de idosos em Manaus, Amazonas, Brasil

Abstract: A avaliação do impacto da vacinação contra a COVID-19 em idosos é escassa, sobretudo em um cenário com predomínio da variante Gama. O objetivo deste estudo foi avaliar a cobertura vacinal e sua relação com mudanças no padrão de internações e óbitos por COVID-19 em idosos de Manaus, Amazonas, Brasil. Este é um estudo ecológico com dados de internações e óbitos do Ministério da Saúde que avaliou a cobertura vacinal, mediante esquema com duas doses, além de dois regimes de vacinação associados a significativo efe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
2
5
0
6
Order By: Relevance
“…These data corroborate the findings of other studies, which showed a significant decline in the number of cases among the elderly accompanying the commencement of vaccination, with a consequent tendency for rejuvenation in hospitalizations and deaths [9][10][11] . Data from the Ministry of Health on COVID-19 showed that between the beginning of January and the end of June 2021 there was a reduction in the average age among hospitalized cases from 62.3 to 52.5 years old, and from 71.4 to 61.2 years old for deaths in Brazil 12 .…”
Section: Discussionsupporting
confidence: 91%
“…These data corroborate the findings of other studies, which showed a significant decline in the number of cases among the elderly accompanying the commencement of vaccination, with a consequent tendency for rejuvenation in hospitalizations and deaths [9][10][11] . Data from the Ministry of Health on COVID-19 showed that between the beginning of January and the end of June 2021 there was a reduction in the average age among hospitalized cases from 62.3 to 52.5 years old, and from 71.4 to 61.2 years old for deaths in Brazil 12 .…”
Section: Discussionsupporting
confidence: 91%
“…The other studies compare all groups of hospitalized patients. However, when it comes to the change in profile of the vaccinated hospitalized patients, studies have observed the change in pattern, as well as in young men with no comorbidities that were not vaccinated [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Este cenário acarretou um sistema de saúde nacional próximo ao colapso (Brasil, 2020). A partir de 2021, com a chegada da imunização contra a COVID-19, observou-se a redução da mortalidade geral da população, e esta foi recomendada, no mundo todo, para gestantes e puérperas (Orellana et al, 2022). Neste contexto, o distanciamento social, a imunização para a doença, o uso de máscara e outras medidas, se tornaram as principais formas de proteção para esta população (Brasil, 2021).…”
Section: Introductionunclassified